Passive samplers : development and application in monitoring organic micropollutants in South African water bodies and wastewater - Amdany, Robert (My University, 2014)
Annually, the global environment receives enormous amounts of persistent organic pollutants (POPs) that include polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs), in addition to polycyclic aromatic hydrocarbons (PAHs). Their ubiquity has made them identifiable contaminants in almost every environmental compartment of the global system. In particular, aquatic systems have been adversely affected by these pollutants. Therefore, effective monitoring, both in ground and surface water, that can reliably assess their environmental impacts is required. Passive samplers have been proposed as suitable options to the traditional grab/spot/bottle sampling approach because they simultaneously sample, isolate and enrich target analytes. Moreover, apart from successfully detecting very low water dissolved analyte concentrations (trace and sub-trace levels), the devices can also provide time weighted average (TWA) concentrations that take into account episodic events. This is usually not practical with other sampling techniques.
Keywords: Pollutants - South Africa.; Water - Pollution - South Africa.; Water supply - South Africa.